2021
DOI: 10.1038/s41586-021-04128-4
|View full text |Cite
|
Sign up to set email alerts
|

Megastudies improve the impact of applied behavioural science

Abstract: Milkman et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(111 citation statements)
references
References 29 publications
4
106
1
Order By: Relevance
“…Nevertheless, Mertens et al focus their message on the average effect size estimated without adjusting for publication bias, concluding that "our results show that choice architecture interventions promote behavior change with a small to medium effect size of Cohen's d = 0.45"(p. 1). We argue that this effect size is implausibly large which could be misleading and further strengthen researchers' and practitioners' overoptimistic expectations 3,4 about the impact of nudges. Furthermore, the authors focus their conclusions on this average value and on subgroups, leaving aside the large degree of unexplained heterogeneity 5 in apparent effects across published studies.…”
mentioning
confidence: 75%
“…Nevertheless, Mertens et al focus their message on the average effect size estimated without adjusting for publication bias, concluding that "our results show that choice architecture interventions promote behavior change with a small to medium effect size of Cohen's d = 0.45"(p. 1). We argue that this effect size is implausibly large which could be misleading and further strengthen researchers' and practitioners' overoptimistic expectations 3,4 about the impact of nudges. Furthermore, the authors focus their conclusions on this average value and on subgroups, leaving aside the large degree of unexplained heterogeneity 5 in apparent effects across published studies.…”
mentioning
confidence: 75%
“…Similarly, a multicountry randomized experiment by Moehring et al finds that providing individuals information about the share of their network that is accepting of vaccines influences individuals’ own vaccination intentions ( Moehring et al, 2000 ). While not focused on COVID-19 vaccination, two recent studies by Milkman et al find that text-message-based nudges leveraging loss-aversion and social pressure can increase flu vaccination by up to 5 percentage points ( Milkman et al, 2021b ; Milkman et al, 2021a ). Taken together, our results contribute to research on behavioral science strategies for addressing COVID-19 vaccine hesitancy by revealing changes to side-effect framing as another additional nudge-based pathway for impact.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing public concerns over vaccine side-effects will be a key component of efforts to improve vaccine use in the United States, United Kingdom, and globally – especially with recommendations for ongoing booster doses. Several recent behavioral sciences studies investigating this topic have found that small financial incentives and reminders can improve COVID-19 and flu vaccine uptake ( Campos-Mercade et al, 2021 ; Milkman et al, 2021b ; Milkman et al, 2021a ; Dai et al, 2021 ; Klüver et al, 2021 ; Santos et al, 2021 ). As another distinct ‘nudge’ pathway, there is a large body of evidence in health communication and the behavioral sciences that shows that how risks are framed and presented to individuals can also affect their perceptions of its severity and ultimately their behavior ( Bonner et al, 2021 ; Trevena et al, 2013 ; Zipkin et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although behavior analysts may find the concept familiar, BA boosting possesses the merit of providing an operational account of the conditions for creating long-lasting behavior change once the effects of nudging fade out. For example, only 8% of interventions a megastudy (i.e., a massive field experiment testing out several concurrent behavioral interventions in the same population and in a comparable way) aimed at informing policy for encouraging physical exercise were still found measurable and significant after 4 weeks from rollout (Milkman et al, 2021 ).…”
Section: Nudging and Boosting: Interventions Of Choice Architecturementioning
confidence: 99%